2008
DOI: 10.1038/oby.2008.55
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat Accumulation Induced by a High‐fat Diet Causes the Atrophy of Mesenteric Lymph Nodes in Obese Mice

Abstract: objective: A high intake of fat in the diet plays a crucial role in promoting obesity and obesity-related pathologies, and especially visceral obesity is closely associated with obesity-related complications. Because adipose tissue is anatomically associated with lymph nodes, the secondary lymphoid organ, we hypothesized that fat tissue-derived factors may influence the cellularity of lymphoid tissue embedded in fat. Methods and Procedures: Mesenteric and inguinal lymph nodes were isolated from obese mice fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 42 publications
8
44
2
Order By: Relevance
“…The authors suggested that factors emanating from the mesenteric fat, such as free fatty acids, induced apoptosis of lymphocytes residing in MLN. 11 In this study, we also show that immunity in gut-associated lymph tissue is altered. More specifically, MLN immune cells of obese JCR:LA-cp rats produced higher amounts of IL-1b, suggesting a heightened inflammatory response as compared with peripheral immune cells and are most likely influenced by the inflammatory environment of the mesenteric adipose tissue.…”
Section: Potential Influence Of Adipose Tissue On Mln Immune Cellsmentioning
confidence: 56%
See 2 more Smart Citations
“…The authors suggested that factors emanating from the mesenteric fat, such as free fatty acids, induced apoptosis of lymphocytes residing in MLN. 11 In this study, we also show that immunity in gut-associated lymph tissue is altered. More specifically, MLN immune cells of obese JCR:LA-cp rats produced higher amounts of IL-1b, suggesting a heightened inflammatory response as compared with peripheral immune cells and are most likely influenced by the inflammatory environment of the mesenteric adipose tissue.…”
Section: Potential Influence Of Adipose Tissue On Mln Immune Cellsmentioning
confidence: 56%
“…1 To date, only one study has investigated the impact of obesity on MLN immune cell function. Kim et al 11 reported that high fat-fed mice had smaller MLN and subsequently fewer immune cells. The authors suggested that factors emanating from the mesenteric fat, such as free fatty acids, induced apoptosis of lymphocytes residing in MLN.…”
Section: Potential Influence Of Adipose Tissue On Mln Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the observed high levels for OPN in MAT and EAT from HF/n-3 mice could be derived from T cells and/or adipocytes. It is important to note that MAT includes MLN, which are involved in immune response, whereas EAT does not contain lymph nodes (32,52). MLN can enlarge due to the expansion of MLN immune cells upon immune responses of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the highest energetic intake resulted in the greater rate of weight gain observed in animals fed a diet containing pequi (CHARRONDIERE et al, 2004;LIMA et al, 2007;STRIJBOSCH et al, 2008). Moreover, the intake of a high-fat diet has been associated with overweight in mice, thus the higher weight gain in the animals in the experimental groups can be the result of high lipid content of pequi added to diet (KIM et al, 2008;HONG et al, 2009). …”
Section: Discussionmentioning
confidence: 99%